2012
DOI: 10.1073/pnas.1120510109
|View full text |Cite
|
Sign up to set email alerts
|

Subpixel colocalization reveals amyloid precursor protein-dependent kinesin-1 and dynein association with axonal vesicles

Abstract: Intracellular transport of vesicles and organelles along microtubules is powered by kinesin and cytoplasmic dynein molecular motors. Both motors can attach to the same cargo and thus must be coordinated to ensure proper distribution of intracellular materials. Although a number of hypotheses have been proposed to explain how these motors are coordinated, considerable uncertainty remains, in part because of the absence of methods for assessing motor subunit composition on individual vesicular cargos. We develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 47 publications
3
34
0
Order By: Relevance
“…In addition to adaptor and signaling proteins, APP CTFs are also implicated in interactions with motor proteins such as kinesin, myosin, and dynein (Cottrell et al, 2005;Goldstein, 2012), thereby possibly controlling their own transport (Rodrigues et al, 2012). For example, kinesin-1 localizes to APP-positive axonal vesicles (Szpankowski et al, 2012), and kinesin-1 may interact with APP either directly or indirectly via JIP1 (Chiba et al, 2014;Goldstein, 2012;Kamal et al, 2001;Lazarov et al, 2005). Intriguingly, striking evidence has been reported that JIP1 can directly control anterograde or retrograde directions of APP transport by controlling the activities of kinesin-1 and dynein (Fu and Holzbaur, 2013).…”
Section: App Proteolytic Products: Unique Proteins With Specialized Fmentioning
confidence: 99%
“…In addition to adaptor and signaling proteins, APP CTFs are also implicated in interactions with motor proteins such as kinesin, myosin, and dynein (Cottrell et al, 2005;Goldstein, 2012), thereby possibly controlling their own transport (Rodrigues et al, 2012). For example, kinesin-1 localizes to APP-positive axonal vesicles (Szpankowski et al, 2012), and kinesin-1 may interact with APP either directly or indirectly via JIP1 (Chiba et al, 2014;Goldstein, 2012;Kamal et al, 2001;Lazarov et al, 2005). Intriguingly, striking evidence has been reported that JIP1 can directly control anterograde or retrograde directions of APP transport by controlling the activities of kinesin-1 and dynein (Fu and Holzbaur, 2013).…”
Section: App Proteolytic Products: Unique Proteins With Specialized Fmentioning
confidence: 99%
“…3. For each image in the Z-stack (cargo, motor 1 and motor 2; generated in step 4.2.14) determine the X-Y coordinates and intensity amplitudes for each fluorescent puncta using an established algorithm to fit 2D Gaussians to the point spread function that represents each point source in each of the three channels 16,20,21 ( Figure 2D).…”
Section: "Cargo Mapping" Analysesmentioning
confidence: 99%
“…To obtain the X-Y coordinates, a custom built MATLAB software package called "Motor Colocalization" was developed 16,20 , which incorporates a Gaussian fitting algorithm developed by Jaqaman, Danuser and colleagues [21][22][23] . The software package and detailed instructions for its use can be obtained upon request.…”
Section: Notementioning
confidence: 99%
See 2 more Smart Citations